Reverse resistance to immune checkpoint inhibitor in a patient with recurrent cardia cancer by intratumoral injection of recombinant human adenovirus type 5: a case report and literature review - Zhao, Qiu; Xiao, Min; Ma, Jian; Fu, Cong; Gao, Qianqian (Frontiers in Oncology, 2024)
Advanced metastatic cardia cancer is an intractable malignance with poor prognosis. It is often accompanied by upper digestive tract obstruction, which seriously affects the quality of patients. Therefore, effective relief of eating obstruction is an important goal in the treatment of cardia cancer. Immune checkpoint inhibitors (ICIs) have shown significant efficacy in cardia cancer, but only a small percentage of patients will benefit from them due to immune resistance. Oncolytic viruses have been shown to enhance the efficacy of ICIs by altering the immune microenvironment. This indicates that oncolytic virus has the potential value of overcoming the immune resistance of cardia cancer. Here, we present a case with local recurrent and multiple metastatic cardia cancer accompanied by eating obstruction. After 4 cycles of chemotherapy plus ICI therapy, the patient´s metastases were significant shrink, but the recurrent carida lesion were almost unchanged. Then we implemented exploratory local injection of recombinant human adenovirus type 5(H101) into recurrent cardia lesion by painless gastroscopy. Surprisingly, the cardia lesion shrank significantly, and the eating obstruction was greatly relieved. We also observed a significant increase of infiltrated CD4+T cells in biopsy tissues after H101 treatment. Our study not only conformed the value of oncolytic viruses to reverse ICI resistance in patients with gastric cancer, but also revealed its underlying impact on immune microenvironment.